Metataxonomic Profiling of Native and Starter Microbiota During Ripening of Gouda Cheese Made With Listeria monocytogenes-Contaminated Unpasteurized Milk - Salazar, Joelle K.; Gonsalves, Lauren J.; Fay, Megan; Ramachandran, Padmini; Schill, Kristin M.; Tortorello, Mary Lou (Frontiers in Microbiology, 2021)
Unpasteurized milk is used to produce aged artisanal cheeses, which presents a safety concern due to possible contamination with foodborne pathogens, especially Listeria monocytogenes. The objective of this study was to examine the composition of the bacterial community in unpasteurized milk used to prepare Gouda cheese artificially contaminated with L. monocytogenes ( 1 log CFU/mL), and assess the community dynamics and their potential interaction with L. monocytogenes during a 90-day ripening period using targeted 16S rRNA sequencing. The diversity of bacterial taxa in three batches of unpasteurized milk was not significantly different, and the microbiomes were dominated by species of Lactococcus, Streptomyces, Staphylococcus, and Pseudomonas. The highest relative abundances were observed for P. fluorescens (31.84-78.80%) and unidentified operational taxonomic units (OTUs) of Pseudomonas (7.56-45.27%). After manufacture, both with and without L. monocytogenes-contaminated unpasteurized milk, Gouda cheese was dominated by starter culture bacteria (including Lactococcus lactis subsp. cremoris, lactis, lactis bv. diacetylactis, and Streptococcus thermophilus), in addition to unassigned members in the taxa L. lactis and Streptococcus. During ripening there was an overall decrease in L. lactis abundance and an increase in the number of taxa with relative abundances >0.1%. After 90-day ripening, a total of 82 and 81 taxa were identified in the Gouda cheese with and without L. monocytogenes, respectively. Of the identified taxa after ripening, 31 (Gouda cheese with L. monocytogenes) and 56 Gouda cheese without L. monocytogenes) taxa had relative abundances >0.1%; 31 were shared between the two types of Gouda cheese, and 25 were unique to the Gouda cheese without added L. monocytogenes. No unique taxa were identified in the Gouda cheese with the added L. monocytogenes. This study provides information on the dynamics of the bacterial community in Gouda cheese during ripening, both with and without the addition of L. monocytogenes.